Assessment of oat varieties with different levels of breeding refinement from the Vavilov Institute’s collection applying the method of metabolomic profiling - I. G. Loskutov; T. V. Shelenga; A. V. Konarev; V. I. Khoreva; Yu. A. Kerv; E. V. Blinova; A. A. Gnutikov; A. V. Rodionov; L. L. Malyshev (Труды по прикладной ботанике, генетике и селекции)
Metabolomic profiling data obtained through gas chromatography coupled with mass spectrometry are presented. Thirty oat accessions from the collection of the N.I. Vavilov Institute of Plant Genetic resources (VIR) served as the material for the research. Those accessions of Russian and French origin showed different degrees of breeding refinement: from local landraces (the early 1920s) and primitive cultigens (1920–1930s) to modern improved cultivars. Twenty-seven hulled and three naked oat varieties were selected for the study.The main objective of the work was to identify differences among common oat varieties with different degrees of breeding refinement at the level of metabolomic profiles. The resulting data reflected the metabolic state of oat genotypes with different ecogeographic backgrounds. They were compared to assess the content of main metabolite groups important for the formation of the crop’s stress resistance traits as well as nutritional, medicinal and dietary properties of oat grain products. The most informative indicators were identified (fucosterol, chiro-inositol, xylitol; undecylic, threonic, glutamic, ribonic and phosphoric acids; sorbose, fructose, glucose-3-phosphate, and myo-inositol), which helped to make statistically significant differentiation among oat accessions of different origin with various degrees of breeding refinement. Comparing metabolomic profiles of different oat variety groups (landraces, primitive cultigens, and modern cultivars, developed by Russian and French breeders) mirrored distinctive features of the trends followed by different plant breeding schools.This study showed that breeding efforts to improve biochemical indicators in oat grain would require the use of the genetic diversity found in landraces and primitive cultigens collected or developed in the 1920–1930s. This diversity is still preserved and maintained in the global germplasm collection at VIR.